THE EFFECT OF THREE FOLD MODEL OF ROLE PLAY TECHNIQUE IN SPEAKING NARRATIVE TEXT - Dwi Maya; Masitowarni Siregar (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2012)
ABSTRACT The objective of the study was to investigate the use of Three Fold of role play significantly affected students’ speaking competence. This study was conducted by using experimental design. The population was all students of grade XI of SMA PAB 8 SAENTIS with the total number of the students was 120 students. There were 60 students taken as the sample by using cluster random sampling. The students were divided into two groups namely  experimental and control groups. The experimental group was taught by using three fold model of role play while the control group was taught without using three fold of role play. The instrument for collecting data was in the form of oral test. The mean score of post test in experimental group (68,13) is higher than the control group (59,1). The score of experimental group showed that the students’ achievement increases significantly. Dealing the data above, it was found that the use of three fold model of role play affects students’ competence on speaking.   Keywords: three fold model, role play, narrative text, speaking